Design of a Novel Ring VCO with low Phase Noise and High frequency range - Taghizadeh, Maryam; Taghizadeh, Parisa; Taghizadeh, Saeid; Kamaly, Abbas; Emamghorashi, Seyed Ali (International Journal of Computer Sciences and Engineering, 2025)
In this paper a ring VCO with high frequency range and low phase noise in 0.18 um CMOS technology is presented. In the proposed VCO, two techniques including current control and forward bias of body is implemented to increase the range of frequency. It is shown that forward bias of the body of control transistor cause to increase the frequency range noticeably. Moreover, by adding an inductor in the body of control transistor, the phase noise is decreased as well. The phase noise in 1 MHz offset frequency is -90 dBc/Hz and the frequency range is 2-14 GHz.